The Acceptance of Mobile Learning: A Case Study of 3D Simulation Android App for Learning Physics - Lisana, Lisana; Suciadi, Marcellinus Ferdinand (International Journal of Interactive Mobile Technologies (iJIM), 2021)
This study investigates the adoption of the mobile learning, 3D simulation Android app, as an innovative tool for learning in physics for high school students. The factors affecting the acceptance of mobile learning are also determined in this study. The proposed research model employs two constructs, Perceived Usefulness and Perceived Ease of Use, from Technology Acceptance Model (TAM) as a baseline and adds another relevant factor based on prior mobile learning adoption research, Perceived Enjoyment. Data are collected through questionnaires distributed to 50 high school students using Google Forms. Structural equation modeling (SEM) is used to analyze and develop the research model. The study finds that Perceived Enjoyment becomes the most influencing factor considered by high school students to use mobile learning, 3D simulation Android app, followed by Perceived Usefulness. However, the Perceived Ease of Use factor does not significantly influence the acceptance of the 3D simulation Android app.